Heat Unit Establishment as Harvest Criteria on “Mas Kirana” Banana at Various Times of Anthesis - Muhammad Syaifuddin Abdurrohim; Winarso Drajat Widodo; Ketty Suketi (Journal of Tropical Crop Science, 2018)
The method for determining the appropriate time to harvest banana could affect the shelf life and quality of banana fruits during storage. The objectives of this study were to establish the heat unit as harvesting criteria of banana “Mas Kirana” and to evaluate how heat unit affects fruit shelf life and postharvest maturity characteristics. The research was conducted at PTPN VIII Parakansalak Plantation, Sukabumi, West Java, Indonesia, in November 2017 to February 2018. Laboratory analysis was conducted in Postharvest Laboratory, Department of Agronomy and Horticulture IPB in February to April 2018. The experiment was organized in a completely randomized design with a single factor of eight different flower tagging times after anthesis. Each treatment was replicated five times totaling 40 experimental units. The results showed that the different times of anthesis did not affect fruit size, weight per hand, number of fruits per hand and weight per fruit. Different time of anthesis did not affect respiration rate, fruit shelf life, physical and chemical quality. The minimum heat unit of 650ºC degree days can be used as harvesting criteria for banana “Mas Kirana”. The number of day after anthesis was 39 to 43 with fruit shelf life of 12 to 16 days.